Do Market Pressures Induce Economic Efficiency? The Case of Slovenian Manufacturing, 1994-2001 - Orazem, Peter F. (2012)
Using a unique longitudinal data set on all manufacturing firms in Slovenia from 1994 to 2001, this article analyzes how firm efficiency changed in response to changing competitive pressures associated with the transition to market. Results show that the period was one of atypically rapid growth of total factor productivity (TFP). The rise in firm efficiency occurs across almost all industries and firm types: large or small, state or private, domestic or foreign owned. Changes in firm ownership type have no direct impact on firm efficiency. However, increased market competition related to rising market share of private firms, new market entrants, foreign-owned firms, and international trade raises TFP across all firms in an industry, whether private or state owned. In addition, competitive pressures that sort out inefficient firms of all types and retain the most efficient, coupled with the entry of new private firms that are at least as efficient as surviving firms, prove to be the major source of TFP gains. Results strongly confirm that market competition fosters efficiency.